PENGARUH PENGETAHUAN KEWIRAUSAHAAN, KEPRIBADIAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Saragih, Nawary; Purba, Saut; Purba, Betniar (Jurnal Manajemen dan Bisnis, 2022)
The purpose of this research is to find out how big the influence of Entrepreneurship Knowledge, Personality and Family Environment on Entrepreneurial Interest of Students of the Faculty of Economics, Santo Thomas Catholic University, Medan. The type of research used is descriptive and quantitative. The research sample was 40 respondents using a census sampling method from the population based on respondents who answered the questionnaire as training participants on research data processing with Microsoft SPSS (Statistical Program for Social Science). The required data was collected through answers from online questionnaires. The data analysis method used was multiple linear regression analysis. The results of the study of the Entrepreneurial Knowledge variable partially positive and significant effect on Entrepreneurial Interest, the Personality variable partially has a negative effect, but is significant on Entrepreneurial Interest, the Family Environment variable partially has a positive and significant effect on Student Entrepreneurial Interest. Entrepreneurial knowledge, personality and family environment have a significant effect on Student Entrepreneurial Interest. Variations in entrepreneurial knowledge, personality and family environment are able to explain variations in Student Entrepreneurial Interests by 95.1%. Recommended; because the Personality variable partially has a negative but significant effect on Student Entrepreneurial Interest, then to support this personality variable for students there must be support from the family and an increase in curriculum competence from Entrepreneurship Courses. There are still many reasons that students are not interested in entrepreneurship, so to overcome them, it is appropriate for the institution to review the availability of teaching and learning facilities that really help students to master entrepreneurship material and assist lecturers in conveying knowledge that can support the growth of their intention to become entrepreneurs now and in the future they are free from unemployment. For further research, it is better to add specific or distinctive indicators from this study that can support personality variables.